A 5-GHz LC VCO with digital AAC and AFBS for 2.4 GHz ZigBee transceiver applications. Issue 6 (June 2015) - Li, Di; Yang, Yin-Tang; Zhu, Zhang-Ming; Shi, Zuo-Chen
Abstract A 5 GHz LC VCO (voltage-controlled oscillator) with automatic amplitude control (AAC) and automatic frequency-band selection (AFBS) for 2.4 GHz ZigBee transceivers is presented. Instead of continuous feedback loop, an alternative amplitude calibration scheme is proposed in this paper to alleviate the deficiencies inherent in the conventional approach. It helps to keep the VCO at optimum amplitude to avoid saturation of the cross-coupled transistors and therefore stabilizes the phase noise performance over process, voltage and temperature variations. For the ZigBee application with 16 frequency channels, a coarse tuning loop is added in this work to implement the frequency-band selection using the AFBS mechanism. The VCO core and the digital AAC, AFBS modules have been fully integrated in a 2.4 GHz ZigBee transceiver which was fabricated in a 0.18 μm RF-CMOS technology. The current consumption is 4.7 mA at 4.85 GHz with 1.8 V power supply and a chip area of about 0.285 mm2 is occupied. The VCO is capable of operating from 4.67 GHz to 5.18 GHz and the measured phase-noise level is –120 dBc/Hz at 1 MHz offset from a 4.85 GHz carrier. The tuning sensitivity KVCO of the VCO is about 78 MHz/V with 0.9 V control voltage.